Preferensi Hijauan Pakan Gajah Sumatera (Elephas maximus sumatranus): Studi Kasus di Kawasan Seblat - Syarifuddin, Hutwan (Fakultas Peternakan Universitas Jambi, 2008)
The research has purposed were to know forages of the gajah Sumatera (Elephas maximus sumatranus) preference. Data primer was calculated with direct method in field with vegetation analysis. The result showed that most fodder types were Air Tenang (225). Air Senaba and Air Sabai (215) were similar. Batu Ampar (213), Simpang Tiga (207). Air Riki was lowest (197). The sum of elephant forages were in Air Tenang (70 types), Air Senaba (67 types), Simpang Tiga (66 types), Air Sabai (64 types), Air Riki (63 types) and Batu Ampar (59 types). The forages type was liked as: Colocasia gigantea, Imperata cylindrica, Cynodon dactylon and Ichnanthus vicinus, Angiopteris avecta, Knema sp, Macaranga gigantea, Macaranga pruinosa, Parkia speciosa, Mallotus paniculatus, and Arthocarpus elasticus.